2020
DOI: 10.2499/p15738coll2.134179
|View full text |Cite
|
Sign up to set email alerts
|

The effects of COVID-19 policies on livelihoods and food security of smallholder farm households in Nigeria: Descriptive results from a phone survey

Abstract: The International Food Policy Research Institute (IFPRI), a CGIAR Research Center established in 1975, provides research-based policy solutions to sustainably reduce poverty and end hunger and malnutrition. IFPRI's strategic research aims to foster a climate-resilient and sustainable food supply; promote healthy diets and nutrition for all; build inclusive and efficient markets, trade systems, and food industries; transform agricultural and rural economies; and strengthen institutions and governance. Gender is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 13 publications
(15 reference statements)
2
23
0
Order By: Relevance
“…About 65% households interviewed was found to rationed food they eat, while some skip meals or go for low-cost food due to low income caused by lockdown ordered by the government to prevent the spread of the disease in the country. This was in agreement with Balana et al (2020) who reported a significant reduction of consumption of proteins (eggs, meat, and dairy products) and fruits among smallholder farming households in Nigeria due to COVID-19 outbreak.…”
Section: Potential Effects Of Covid-19 On Dietary Intakesupporting
confidence: 92%
See 2 more Smart Citations
“…About 65% households interviewed was found to rationed food they eat, while some skip meals or go for low-cost food due to low income caused by lockdown ordered by the government to prevent the spread of the disease in the country. This was in agreement with Balana et al (2020) who reported a significant reduction of consumption of proteins (eggs, meat, and dairy products) and fruits among smallholder farming households in Nigeria due to COVID-19 outbreak.…”
Section: Potential Effects Of Covid-19 On Dietary Intakesupporting
confidence: 92%
“…The provision of food has always been a challenge facing mankind (Kansiime et al 2020) even before COVID-19 pandemic. Few available studies (such as: Balana et al 2020, Amare et al 2020, Swinnen and McDermott 2020, Schmidhuber et al 2020, UN 2020, Torero 2020, FAO 2020c have shown that COVID-2019 is negatively affecting agriculture through food supply and demand gap deficit, which is directly linked to food insecurity. Most current assessments generally predict a contraction in both supply of and demand for agricultural products as well as possible disruptions in trade and logistics in the long-run.…”
Section: Empirical Literature Review On Covid-19 Outbreak On Agricultmentioning
confidence: 99%
See 1 more Smart Citation
“…The restrictive measures towards containing the spread of COVID-19 infections have seriously affected the agricultural workforce and jeopardized food security across the globe (Bochtis et al, 2020), and the effects have been more severe in low and middle-income countries like Nigeria. The impacts of COVID-19 pandemic according to Balana et al (2020) were felt in the form of job and income losses, food insecurity, and rising food prices.…”
Section: Impact Of Covid-19 Pandemic On Crop Production In Nigeriamentioning
confidence: 99%
“…More than 200 countries and territories have been affected by COVID-19, with major outbreaks occurring in Brazil, Russia, India, Mexico, Peru, South Africa, Western Europe, and the United States (Stawicki et al, 2020). The presence of coronavirus in Nigeria was first reported on 27 February 2020, and since then the cases have risen to over 67,000 and about 1,200 fatalities by the end of November 2020 (Balana et al, 2020). As of 10 th June 2021, a total of 167,027 cases have been confirmed, 163,413 cases have been discharged, and 2,117 deaths recorded in the 36 states of Nigeria and the Federal Capital Territory (NCDC, 2021).…”
Section: Introductionmentioning
confidence: 99%